2003
DOI: 10.1364/ol.28.002437
|View full text |Cite
|
Sign up to set email alerts
|

Photonic molecule lasing

Abstract: Lasing at resonantly coupled whispering-gallery mode frequencies is observed in photonic molecules consisting of bispheres of 4.2 and 5.1 microm in diameter placed in a silicon V-groove. We examine spatial profiles of photonic molecule modes by use of frequency-resolved imaging and reveal bonding and antibonding mode features. From the lasing threshold characteristics, we quantitatively measure the quality factor and the spontaneous-emission coupling ratio of the photonic molecule modes and confirm that strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
47
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…We also note that while absorption will degrade the strength of the resonance, microspheres containing gain materials can in principle enhance the resonant force, and the effect should be most interesting when the WGM starts lasing. 10 These would be interesting topics for further studies.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…We also note that while absorption will degrade the strength of the resonance, microspheres containing gain materials can in principle enhance the resonant force, and the effect should be most interesting when the WGM starts lasing. 10 These would be interesting topics for further studies.…”
mentioning
confidence: 96%
“…The strength of the optical forces can be enhanced by orders of magnitude when a MDR is excited. As microsphere cavities are emerging as an alternative to the photonic crystal in controlling light, [8][9][10] the MDR-force may be deployed for the manipulation of a microsphere cluster.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current state-of-the-art, the difficulties in collecting identical microspheres limit the experiments on tight binding photonic modes to "photonic molecules" consisting of a small number of particles. 10,11,12,13,14,15 The sorting scheme we proposed may help to collect a larger number of microspheres with size-dispersion fulfilling the stringent optical requirements, paving the way to go beyond small "photonic molecules" to extended photonic crystals, coupled resonator optical waveguides, and other structures.…”
mentioning
confidence: 99%
“…Recent studies of optical mode structure in small coupled spherical microcavities [1][2][3][4][5] (photonic molecules, PMs) have led to the observation of a modified electromagnetic field distribution that differs significantly from what would be obtained for a single microcavity. Experimental 2,4 and theoretical 1,3 investigations showed that, depending on the orientation of the PM, whispering gallery modes (WGMs) of a monosphere can be split into two broadened modes of lower quality factor ͑Q͒.…”
mentioning
confidence: 99%